Pelaksanaan Eksekusi Atas Jaminan Fidusia Kendaraan Bermotor pada PT. Bank Nagari Cabang Utama Sumatera Barat - Mardius, Mardius; Hidayatullah, Hidayatullah; Supeno, Supeno (Universitas Batanghari Jambi, 2025)
The Fiduciary Guarantee Law has the main objective to provide legal certainty for the execution of the guarantee, so that the execution can be carried out properly. Based on these reasons, the problems that will be studied in this study are about the practice of executing motor vehicle fiduciary guarantees and the obstacles in implementing the execution of motor vehicle fiduciary guarantees. The approach method used is the sociological legal approach and the specifications used in this study are descriptive research. Based on the results of the study, it can be concluded that the execution of the object of motor vehicle fiduciary guarantees carried out through underhand sales with the agreement of the creditor and debtor, the debtor himself sells his guarantee if there is a default by the debtor. The execution of motor vehicle fiduciary guarantees is carried out against defaulting debtors. The execution in this case ended with an execution application made by the creditor (Bank Nagari) to the district court, because here the creditor did not complete according to the agreement with the underhand sale that had been previously agreed with the creditor was not achieved. So the last resort taken by the creditor (Bank Nagari) was once again to submit an execution application to the court which ended with an auction at the auction body for the object of the motor vehicle fiduciary guarantee. Before execution, there are many obstacles faced by creditors, one of which is that the debtor (Rajal) does not want to cooperate in the execution process because he does not want to sign and hand over the fiduciary guarantee object which has been in default/or breach of promise.